Movement Analysis and Fatigue Life Analysis of the Plough Chain of Coal Plough - Mao Jun; Yao Xu; Chen Hongyue (Jixie chuandong)
According to the work situation of coal plough,considering the plough cut resistance,friction resistance,pre tight force of plough chain,sprocket of polygon effect,and the effect of the force produced by speed changes on sprocket and so on in actual work process,the dynamics model with appropriate simplified of the coal plough is established. By using the Matlab,the simulation analysis is carried out,the time course of plough chain tension and speed in different condition plough cut resistance are got. By using the Miner fatigue damage theory,the fatigue life analysis of plough chain of coal plough is carried out. A basis for the reliability analysis of coal plough working condition and coal plough chain is provide by this study.